The Factors Analysis Shaping SMEs: Adoption Intention of Artificial Intelligence Technology - Hardinata, Satria; Utami, Christina Whidya; Yoseva Maria Sumaji (International Business Management - Universitas Ciputra, 2024)
Artificial intelligence (AI) technology has become a significant trend today because of its ability to process and analyze data quickly and efficiently. Along with the popularity of artificial intelligence (AI) technology in the past ten years, the trend of research, publications, and patents related to AI has experienced rapid and significant growth. AI technology has offered new opportunities for SMEs to assist in market and consumer behavior analysis, enabling them to accurately identify customer trends and preferences. This study aims to determine factors shaping the interest in adopting SMEs towards AI technology. Based on pre-survey data using the FGD method for 10 SME business owners, 32 independent variables were collected to be examined. The population in this study were SMEs assisted by the Department of Cooperatives, SMEs and Trade of the City of Surabaya, and SMEs assisted by PT. Petrokimia within the 2022 period. The sample of the respondents in this study is set as many as 119 SME business owners of the population. The analytical tool used in this research is exploratory factor analysis. The results of this study indicate that six factors shape SMEs' intentions in adopting AI technology, namely the features of AI technology, the awareness of AI technology, the benefits of AI technology, the support of government and external organizations, the influence of social values, and the anthropomorphism factor.